Career Risk and Market Discipline in Asset Management. (10th June 2019) - Ellul, Andrew; Pagano, Marco; Scognamiglio, Annalisa
Abstract: We establish that the labor market helps discipline asset managers via the impact of fund liquidations on their careers. Using hand-collected data on 1, 948 professionals, we find that top managers working for funds liquidated after persistently poor relative performance suffer demotion coupled with a significant loss in imputed compensation. Scarring effects are absent when liquidations are preceded by normal relative performance or involve mid-level employees. Seen through the lens of a model with moral hazard and adverse selection, these scarring effects can be ascribed to a drop in asset managers' reputation. The findings suggest that performance-induced liquidations supplement compensation-based incentives. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.